2017
DOI: 10.1007/s00221-017-4991-7
|View full text |Cite
|
Sign up to set email alerts
|

Tactile feedback is an effective instrument for the training of grasping with a prosthesis at low- and medium-force levels

Abstract: Grasping is a complex task routinely performed in an anticipatory (feedforward) manner, where sensory feedback is responsible for learning and updating the internal model of grasp dynamics. This study aims at evaluating whether providing a proportional tactile force feedback during the myoelectric control of a prosthesis facilitates learning a stable internal model of the prosthesis force control. Ten able-bodied subjects controlled a sensorized myoelectric prosthesis performing four blocks of consecutive gras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 55 publications
1
44
0
Order By: Relevance
“…Because sensory feedback is merged inversely proportional to each modality's uncertainty 23 , sensory feedback encoding position will likely not significantly augment proprioception of a prosthetic limb unless it matches or exceeds vision's 1% uncertainty 24 or encodes information in a novel way, such as tactile sensation 11,18 or discrete events in grasping 9 . However, our study suggests that sensory feedback encoding prosthetic joint speed may more significantly augment proprioception of a prosthetic limb due to higher uncertainty in visual estimates of limb joint speed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because sensory feedback is merged inversely proportional to each modality's uncertainty 23 , sensory feedback encoding position will likely not significantly augment proprioception of a prosthetic limb unless it matches or exceeds vision's 1% uncertainty 24 or encodes information in a novel way, such as tactile sensation 11,18 or discrete events in grasping 9 . However, our study suggests that sensory feedback encoding prosthetic joint speed may more significantly augment proprioception of a prosthetic limb due to higher uncertainty in visual estimates of limb joint speed.…”
Section: Discussionmentioning
confidence: 99%
“…Sensory feedback remains a research priority for prosthesis users 6 . Several feedback methods have been proposed over the past decades, including vibrotactile [7][8][9][10][11] , electrotactile 8 , skin stretch 7 , audio [12][13][14] and visual 15 modalities 16,17 . More complex feedback modalities like peripheral nerve stimulation 18 and vibration-induced illusory kinesthesia 19 have also been introduced to great effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Addressing the challenges associated with the absence of sensation is a highly active field of study, and attempts to provide prosthesis users with sensory feedback have been reported as early as the 1950s (Siehlow, 1951). More recently, the use of mechanotactile and vibrotactile feedback has been used to provide sensations of proportional tactile force (Marasco et al, 2011;Antfolk et al, 2013;Rombokas et al, 2013;Cipriani et al, 2014;Hebert et al, 2014;De Nunzio et al, 2017), and movement sensation (Sharma et al, 2014;Witteveen et al, 2014;Hasson and Manczurowsky, 2015;Marasco et al, 2018) in both amputee and able-bodied populations. These methods have proven effective in patient performance of tasks such as precise force generation (De Nunzio et al, 2017), force discrimination , stiffness discrimination Witteveen et al, 2014), stimuli localization (Antfolk et al, 2013), and multi-site sensory discrimination (Antfolk et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the use of mechanotactile and vibrotactile feedback has been used to provide sensations of proportional tactile force (Marasco et al, 2011;Antfolk et al, 2013;Rombokas et al, 2013;Cipriani et al, 2014;Hebert et al, 2014;De Nunzio et al, 2017), and movement sensation (Sharma et al, 2014;Witteveen et al, 2014;Hasson and Manczurowsky, 2015;Marasco et al, 2018) in both amputee and able-bodied populations. These methods have proven effective in patient performance of tasks such as precise force generation (De Nunzio et al, 2017), force discrimination , stiffness discrimination Witteveen et al, 2014), stimuli localization (Antfolk et al, 2013), and multi-site sensory discrimination (Antfolk et al, 2013). Other approaches are also being pursued, including electrical stimulation of peripheral nerves (e.g., Christie et al, 2017), electrocutaneous stimulation (e.g., Paredes et al, 2015), and direct cortical stimulation of the primary somatosensory cortex (e.g., Tabot et al, 2013;Hiremath et al, 2017).…”
Section: Introductionmentioning
confidence: 99%